Epitaxial Stress‐Free Growth of High Crystallinity Ferroelectric PbZr0.52Ti0.48O3 on GaN/AlGaN/Si(111) Substrate. Issue 2 (27th November 2017) - Li, Lin; Liao, Zhaoliang; Gauquelin, Nicolas; Nguyen, Minh Duc; Hueting, Raymond J. E.; Gravesteijn, Dirk J.; Lobato, Ivan; Houwman, Evert P.; Lazar, Sorin; Verbeeck, Johan; Koster, Gertjan; Rijnders, Guus
Abstract: Due to its physical properties gallium‐nitride (GaN) is gaining a lot of attention as an emerging semiconductor material in the field of high‐power and high‐frequency electronics applications. Therefore, the improvement in the performance and/or perhaps even extension in functionality of GaN based devices would be highly desirable. The integration of ferroelectric materials such as lead–zirconate–titanate (PbZr x Ti1‐ x O3 ) with GaN has a strong potential to offer such an improvement. However, the large lattice mismatch between PZT and GaN makes the epitaxial growth of Pb(Zr1‐ x Ti x )O3 on GaN a formidable challenge. This work discusses a novel strain relaxation mechanism observed when MgO is used as a buffer layer, with thicknesses down to a single unit cell, inducing epitaxial growth of high crystallinity Pb(Zr0.52 Ti0.48 )O3 (PZT) thin films. The epitaxial PZT films exhibit good ferroelectric properties, showing great promise for future GaN device applications. Abstract : A one‐monolayer MgO buffer layer enables epitaxial growth of highly crystalline, ferroelectric PbZr0.52 Zr0.48 O3 (PZT) on GaN/AlGaN/Si. This layer can completely overcome the lattice mismatch and is found to be not strained to the GaN allowing for the growth of epitaxial, functional PZT, paving a bright path toward oxide‐GaN electronics.